Effect of six weeks resistance training with different exercise order on hematological variables in overweight women - Dariush Sheikholeslami Vatani; Fariba Fallahi; Roonak Tabei (Shahid Beheshti University, 2018)
Purpose: Exercise can lead to various hematological changes and it may be effects on some blood variables.The purpose of present study was to investigate the effects of resistance training with different order onhematological changes (include HGB, HCT, RBC, WBC, MCV, MCH, MCHC, RDW, PLT and MPV) in overweightwomen (BMI= 25-30 Kg/m2).Methods: Thirty-one overweight students (Weight: 71.91 ± 8.28 kg and Height: 160 ± 0.05 cm) wereobjectively selected and randomly divided into three groups: the experimental group 1 (perform exercisesfrom large to small muscles, n= 10), the experimental group 2 (perform exercises from small to large muscles,n= 11) and the control group (without any training program, n= 10). Resistance training consists of 6 weeks(3 sessions per week). The hematological variables were measured in resting conditions before experimentand again after completion of the training period.Results: Findings using by one-way ANOVA revealed there were no significant differences in any of thehematologic variables levels between three groups.Conclusion: In general, results showed that medium-term resistance training program and so changing thesequence of performance of resistance exercise - none of them - do not have any effect on hematologicresponses.